Design & Implementation of Smart Headlamps, Overtaking Assistance for Automobiles using MATLAB - et. al., Glenson Toney, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A large number of accidents occur due to human errors especially during night driving because of temporary blindness caused by the headlights of the oncoming traffic. This can be drastically reduced with the adoption of a Smart Headlamp and overtaking kit, which notifies the driver to judge and make a perfect overtake based on the oncoming traffic and also will suggest safe overtakes. The system will Auto- dim one side of the headlight to avoid high beam blindness for oncoming traffic, this system also recognizes the vehicle in front and decreases the beam to low if the vehicle is in certain specified proximity. The use of cameras to detect objects, vehicles, animals, humans is really helpful as compared to sensors. The accuracy of image data is much more than that of sensor data. With the combination of image data and sensor data the system can operate with greater efficiency.